Karakteristik Japandi untuk Koleksi Citywear for Womenswear and Menswear - Prianka, Dian; Khotania, Devina; Juniati, Ninik (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2023)
Abstract—Inspiration drawn from Japandi's interior design style adjusts the trend forecast from WGSN season Autumn Winter 2023/2024: